Niveles de venta en la Boutique Terra Moda del cantón Ventanas - Coello Ruiz, Kenny Josue (2021)
Sales are substantial so that a company can stand and last over time, without sales a commercial company has no reason to exist and its future is uncertain. The Terra Moda boutique located in the central part of the Ventanas canton, in its last periods has presented unfavorable results in its sales, compared to previous years, for this reason this case study was carried out, where through an interview and a survey of the owner, information was obtained that helped to have a greater perspective and understanding of the situation. From this conversation, in the first instance, some important aspects were distinguished in which the microenterprise has shortcomings and that have an impact on sales, aspects such as advertising and competition; these among other causes that are described in this document. For the development of this case study and in accordance with the subject of our study: Sales levels in the Terra Moda Boutique of the Ventanas canton, the sub-line of research "Marketing and commercialization" of the Faculty of Administration, finance and IT.